Pengembangan E-Modul pada Proses Pembelajaran Instalasi Penerangan Listrik - Mutia Hardika; Elfizon Elfizon (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2021)
This research is motivated by the lack of learning materials provided by the teacher as a guide for students in learning which results in a lack of student initiative to learn independently. Coupled with the policy for online learning during the COVID-19 pandemic, learning in schools is not optimal. This study aims to produce a valid and practical E-Module for Electrical Lighting Installation learning at SMK Negeri 2 Payakumbuh. This study uses research and development methods with a 4D development model. The subjects of this study were students of class XI TITL SMK N 2 Payakumbuh who were registered in the first semester of the 2021/2022 academic year. Based on the results of the study, the validity of the media was obtained with a valid category and material validation was obtained with a valid category. The practicality test with teacher respondents got results in the practical category and respondents from class XI TITL SMK N 2 Payakumbuh stated that the E-Module learning of Electrical Lighting Installation was categorized as very practical. So it can be concluded that the E-Module of Electrical Lighting Installation produced is valid and practical to use in the learning process at school.